Endüstriyel atıksuların biyolojik arıtılabilirliğinin matematik benzeşimi - Ateş, Esra (Fen Bilimleri Enstitüsü, 1991)
Bu çalışmada çözünmüş inert substratın ve partiküler inert substratın aktif çamur sistemleri üzerindeki etkisi incelenmiştir.Birinci bölümde, atıksu içeriğinin aktif çamur sistemlerinin tasarım ve işletilmesindeki önemi vurgulanmıştır. Çalışmanın amaç ve kapsamı açıklanmıştır. İkinci bölümde, biyolojik antılabilirlik teorik olarak ele alınmış ve antılabilirliğe etki eden faktörler belirlenmiştir. Aerobik arıtmanın temel prensipleri çerçevesinde geliştirilen biyolojik antılabilirlik modelleri incelenmiş ve ihmal ettiği konular açıklanmıştır.Üçüncü bölümde, kalıcı parametrelerin benzeşimi incelenmiştir. Çözünmüş inert substrat ile ilgili olarak önerilen kavramlar açıklanmış, aktif çamur sistemlerinde çözünmüş inert ürün süreci üzerinde durulmuş ve inert ürün fraksiyonu (a veya B) formüle edilmiştir. Çözünmüş inert substrat benzeşiminde dönüşüm oranının etkisi incelenmiş ve dönüşüm oranından kaynaklanan hatanın giderilmesi için belirlenen yaklaşım açıklanmıştır. Partiküler inert substrat benzeşiminde dönüşüm oram etkisi incelenmiş, partiküler inert substrat tayini için belirlenen yaklaşımlar belirtilmiştir. Canlılık ve aktivite ile ilgili daha önceki çalışmalar değerlendirilmiş ve biyokitle ölçüm yöntemleri ele alınmıştır.Dördüncü bölümde, ayrışabilir bileşenlerin benzeşimi ile ilgili daha önceki çalışmalar genel olarak değerlendirilmiş, kağıt endüstrisi atıksulan deneysel ve benzeşim sonuçlan incelenmiş, kinetik sabitlerin değişiminin benzeşim sonuçlan üzerindeki etkisi açıklanmıştır. Beşinci bölümde, sürekli sistemlerde çözünmüş inert substrat konsantrasyonunun, çözünmüş inert ürün fraksiyonunun değişiminin sistem karbon giderim verimi üzerindeki etkisi incelenmiştir. Kinetik sabitlerin değişiminin (jl, Kg, Y) bir değerlendirilmesi yapılmıştır ve son bölümde elde edilen çalışma sonuçlan özetlenmiştir.

The world has been the scene of rapid industrialization for the last few ecades. As a result, environmental problems, expecially water pollution have ropped up. Industrial wastewater responsible for the increase of water pollution to great extent are treated mainly by biological wastewater treatment systems, the most ammon of which is activated sludge. The basic components of this, process may e outlined in the following process flow diagram. -5-/x * ) \ /s. o\\j Y^r» *, Qt + Qw T Figüre 1. Typical How Diagram of an Activated Sludge System. xiii CR= S, + Sp + X, + XP + Ss (1) Wherc; CR : Ultimate COD in settled wastcwater Sı: Inert soluble substrate concentration Sp : Inert soluble product concentration Xj: Inert particulates concentration XP : Inert particulate product concentration Ss : Soluble substrate concentration CR' = S, + Sp' + XP + Ss (2) where; CR' = Ultimate COD in filtered wastewater Sp = Inert soluble substrate in filtred wastewater Xp = Inert particulate product in filtred wastewater CODt = C0 - CR where, C0 : Initial COD in settled Wastewater COD2 = S0 - CR where, S0: Initial COD in filtered Wastewater Sp = Yp So where, Yp = Sp / S0 S - s' ACODı Sp SP~ÎCÖÖ; ' bCODı Xp " Xp~îcÖD2 xiv In equation (I), Ss value is supposed to be very low (approximatly 2 3 mg/l) So, the only unkown in equation (1) is X,. We can calculated X, value from this equation by replacing all components calculated above. Emphasis is placed on the basis relating viability concept and on the determination methods. The effect of kinetics constants on the carbon removal efficiency is investigated and it is seen that Kg and Y values have an effect on carbon removal efficiency. In sum, influent substrate concentration affects effluents substrate concentration. There is an minimum 0X value providing minimum effluent COD concentration for each influent concentrations. Sludge age shouldn't be too long not to corrupt sludge settling ability. xvu Definition of organic content of wastewater is very important for the design and the operation of treatment plants. This influent organic content measured as COD is constituted by biological degradable substrate and biological nondegradable substrate, and COD measured in the effluent has biological nondegradable substrate which is produced by biological degradable products and metabolic inert products. The soluble effluent COD of a well operated activated sludge plant is likely to be composed almost entirely of organic matter generated by microbial activity. There is evidence to show that a significant portion of this soluble organic matter is non-degradable and may be due to similar microbial mechanisms. In the literature the generation soluble residual products, (SRP), is explained by the hydrolysis of non-viable cellular materials in the reactor. New experimental methods are developed for the assesment of initial inert soluble COD fraction in wastewaters by identifying and minimizing the inert soluble microbial products interference. In this study, it is supposed that yield of wastewater is equal to yield of glucose (Yw = YG). S0, the effect of yield on soluble inert product is not taken into consideration. This assumption might cause some experimental errors. A new approach is suggested and investigated in this study to overcome these experimental errors. Total particulate organics in activated sludge systems includes three components: Active biomass concentration, (Xa) Slowly degradable particulate organics, (Xs) inert particulate organics, (Xj) Three method have been developed and evaluated to determine inert particulate organics in the influent. The first approach in determining X, is the monitoring of total biomass versus time. Ultimate value of total biomass is composed of the sum of inert particulate substrate in the influent and inert particulate substrate produced by lysis of active biomass in the system, inert particulates are determined by the substraction of inert particulates produced in the system (Xe) from ultimate total biomass (XT) In the second approach separate reactors having settled wastewater, filtered waste water and glucose are operated as batch reactors with addition of sufficient seed microorganism concentration. Total biomass profile is observed with time in these reactors. Inert soluble substrate (Sj) are calculated by using these observations and inert particulate substrate (X,) is computed same as its in the first approach. In the third approach, the experimental procedure defined in the second approach is applied. However the calculation of X, is different in this approach. Calculation steps are as follows: xvi In equation (I), Ss value is supposed to be very low (approximatly 2 3 mg/l) So, the only unkown in equation (1) is X,. We can calculated X, value from this equation by replacing all components calculated above. Emphasis is placed on the basis relating viability concept and on the determination methods. The effect of kinetics constants on the carbon removal efficiency is investigated and it is seen that Kg and Y values have an effect on carbon removal efficiency. In sum, influent substrate concentration affects effluents substrate concentration. There is an minimum 0X value providing minimum effluent COD concentration for each influent concentrations. Sludge age shouldn't be too long not to corrupt sludge settling ability.
Mathematical simulation of biological treatability of industrial wastewaters
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1991
Keywords: Biyolojik arıtma; Endüstriyel atık su; Kağıt endüstrisi; İnert KOİ; Biological treatment; Industrial waste water; Paper industry; Inert COD